Complete Denture with Sectional-Tray Approach in a Microstomia Patient: A Case Report and Literature Review - Fatemeh Soleimani; Negin Yaghoobi; Somayeh Niakan (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Microstomia refers to any significant decrease in the size of the oral cavity. It can cause difficulty in the fabrication of dentures, and the result of this situation shows a significant decline in quality of life. This study describes a treatment method for preparing a complete denture in an edentulous patient with microstomia due to burns. The present study decided to employ a sectional tray and single unit denture considering the hygienic issue and prolonged durability. The major advantage of this scheme is reducing food impaction between different parts. Eventually, the patient was noticeably satisfied, and aesthetic and functional demands were provided.